2008
DOI: 10.1158/0008-5472.can-07-2580
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Alternative Splicing Markers for Ovarian Cancer

Abstract: Intense efforts are currently being directed toward profiling gene expression in the hope of developing better cancer markers and identifying potential drug targets. Here, we present a sensitive new approach for the identification of cancer signatures based on direct high-throughput reverse transcription-PCR validation of alternative splicing events. This layered and integrated system for splicing annotation (LISA) fills a gap between high-throughput microarray studies and high-sensitivity individual gene inve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
131
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 143 publications
(137 citation statements)
references
References 44 publications
4
131
0
2
Order By: Relevance
“…The results indicate that differences between normal and cancer tissues are much smaller than previously thought. Analyzing the expression of a subset of the RefSeq alternative splicing events in RNA extracted from whole ovarian tumors identified 336 cancer-associated ASEs (Klinck et al 2008;Venables et al 2009), while comparison of normal and cancer epithelial or stromal tissues identified a total of 17 cancer-specific ASEs (Supplemental Tables S2, S3, S9). Most of the 336 whole tumor markers affected celltype-specific genes including those linked to cell plasticity (MAP3K7) and cell movement (CEACAM1) (Venables et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results indicate that differences between normal and cancer tissues are much smaller than previously thought. Analyzing the expression of a subset of the RefSeq alternative splicing events in RNA extracted from whole ovarian tumors identified 336 cancer-associated ASEs (Klinck et al 2008;Venables et al 2009), while comparison of normal and cancer epithelial or stromal tissues identified a total of 17 cancer-specific ASEs (Supplemental Tables S2, S3, S9). Most of the 336 whole tumor markers affected celltype-specific genes including those linked to cell plasticity (MAP3K7) and cell movement (CEACAM1) (Venables et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression and, more recently, alternative splicing, a highly regulated and cell-type-specific process, have been found to be globally altered in cancer cells (Sotiriou et al 2006;Klinck et al 2008;Venables et al 2009). Profiling the global expression resulted in several sets of biomarkers capable of detecting cancer subtypes and was particularly successful in differentiating between different breast cancer subtypes (Munirah et al 2011;Prat et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comme ces décisions sont souvent altérées dans certaines pathologies comme le cancer, l'application des connaissances qui expliquent comment les différences d'expression, les mutations et les polymorphismes entre individus contribuent au déve-loppement des maladies et à leur évolution chez l'homme représente un enjeu important au plan médical. Force est de constater que l'incroyable diversité créée par l'épissage alternatif contribue actuellement à l'identification de nouveaux biomarqueurs à potentiel clinique [44]. Il est maintenant permis d'espérer qu'une meilleure caractérisation des isoformes d'épissage et des mécanismes régulant leur production mènera à des traitements innovateurs en vue d'améliorer la santé humaine.…”
Section: Resultsunclassified
“…Other published techniques to determine AS include high throughput RT-PCR [13][14][15] and deep sequencing or RNASeq (short-read high-throughput sequencing) [16][17][18]. Venables et al described a RT-PCR based system that used two sets of primers specific to each identified exon-exon junction and AS events in 600 cancer associated genes [15].…”
Section: Techniques To Profile Alternative Splicingmentioning
confidence: 99%